Ab Initio Study of Electronic Transport in Cubic-HfO2 Grain Boundaries. (5th July 2017) - Degoli, Elena; Luppi, Eleonora; Capron, Nathalie
Abstract : In polycrystalline materials the grain boundaries (GBs) are particularly important as they can act as a sink for atom defects and impurities, which may drive structural transformation of the materials and consequently modify their properties. Characterising the structure and properties of GBs is critical for understanding and controlling material property. Here, we investigated how GBs can modify the structural, electronic, and transport properties of the polycrystalline material H f O 2 . In general, grain boundaries are considered to be detrimental to the physical stability and electronic transport in H f O 2 . Anyway, studying by first principles the two most stable and common types of GBs, the tilt and the twist, we found substantial differences on the impact they have on the material properties. In fact, while tilt defects create channels of different sizes and shapes in hafnia along which the electronic transport is stronger in relation to leakage current through GBs, twist defects create a sort of amorphous structure that tends to resemble the bulk and which is independent of the number of rotated planes/atoms.